Program Bedah Rumah Sebagai Bentuk Sosial Untuk Minimalisir Rumah Tidak Layak Huni - I Nengah Sinarta; Nyoman Nuri Arthana; Komang Deddy Endra Prasandya; Agus Kurniawan (Jurnal Abdi Daya, 2022)
The house is a basic need that must be met for a place of protection from the sun's heat, rain, disease, and animal attacks. This study aims to help the underprivileged so that this program is useful as a social form. Community service activities in Banjar Puragae, Pempatan Village, Rendang District, Karangasem Regency as a form of applying knowledge and experience to minimize uninhabitable houses. A house is said to be well designed and implemented with attention to its users. Through the home renovation program, it is hoped that its implementation will target one of the poorest communities. The survey was conducted using an approach with interviews and observations with village heads and the surrounding community. The house renovation program is one of the efforts to equalize the development and welfare of the poor in remote areas. The problem is that the physical condition of the house is badly damaged and the environment of the house is unfit for habitation. The solution that will be offered is home renovation in the form of social, of course, this program is expected to have a positive impact on the community.